(x-9)(x-1)=12

Simple and best practice solution for (x-9)(x-1)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-9)(x-1)=12 equation:



(x-9)(x-1)=12
We move all terms to the left:
(x-9)(x-1)-(12)=0
We multiply parentheses ..
(+x^2-1x-9x+9)-12=0
We get rid of parentheses
x^2-1x-9x+9-12=0
We add all the numbers together, and all the variables
x^2-10x-3=0
a = 1; b = -10; c = -3;
Δ = b2-4ac
Δ = -102-4·1·(-3)
Δ = 112
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{112}=\sqrt{16*7}=\sqrt{16}*\sqrt{7}=4\sqrt{7}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-10)-4\sqrt{7}}{2*1}=\frac{10-4\sqrt{7}}{2} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-10)+4\sqrt{7}}{2*1}=\frac{10+4\sqrt{7}}{2} $

See similar equations:

| Y=25+8(x) | | .18(y-7)+0.14y=0.04y-2.1 | | 3/8(p-8)+1/2p=(p-6) | | -12n-19=49 | | 2/(x-1)+5=17/(x-1) | | (x-8)(X+4)=(x-4)(x-3) | | 2x(x+3)=32 | | 8(2x-6)=12 | | 4x^2+13x-4x^2=3 | | 4K=12+2z | | -x)+x=22+x | | 8x+2+5x^2=4 | | Y=27000x0.15^5 | | -2z=-68 | | -5x+3(5x-11)=57 | | 3|x|-66=0 | | 5(3m-(2)+4m= | | 2(t+1)=9 | | -1-1(1-7x)=5(2x+8) | | m+15=-18 | | -27=n-14 | | 3x-6=18+4 | | 77+x+26+x-3=180 | | x-(x-12)=58 | | -3(p-(4-2p))=1 | | 11n=22n | | x/20+2=7 | | 3/4x-5=1/2x+9 | | 3(2a+1)=11(a-2 | | -12+b=-10 | | 5+2n=-6+7n | | 6y+2=5y+7=13y-3 |

Equations solver categories